Case Report - Multinodular goiter in a patient with Congenital Hypothyroidism and Bannayan-Riley-Ruvalcaba syndrome: the possible synergic role of TPO and PTEN mutation - Vincenzi, Gaia; Petralia, Ilenia Teresa; Abbate, Marco; Tarantola, Giulia; Meroni, Silvia Laura Carla; Maggiore, Riccardo; Mari, Gilberto; Patricelli, Maria Grazia; Schiavo Lena, Marco; Barera, Graziano; Vigone, Maria Cristina (Frontiers in Endocrinology, 2023)
We report the case of a paediatric female patient affected by Bannayan-Riley-Ruvalcaba syndrome (BRRS) and congenital hypothyroidism (CH) with homozygous mutation of the TPO gene. She underwent total thyroidectomy at the age of seven years because of the development of a multinodular goiter. BRRS patients present an increased risk of benign and malignant thyroid disease since childhood because of inactivating mutation of PTEN, an onco-suppressor gene. Instead, homozygous mutations in the TPO gene can be associated with severe forms of hypothyroidism with goiter; previous studies have described cases of follicular and papillary thyroid cancer in CH patients with TPO mutation despite a perfectly controlled thyroid function with Levothyroxine therapy. This case provides a challenging scenario: mutation of TPO and PTEN may have had a synergic role in the development of multinodular goiter underlining the importance of a tailored surveillance program in these patients, especially during childhood.